2012
DOI: 10.1080/19443994.2012.692042
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption modeling of Orange G dye on mesoporous activated carbon prepared from Algerian date pits using experimental designs

Abstract: A B S T R AC TActivated carbon was prepared from Algerian date pits using physicochemical activation method consisted of zinc chloride (ZnCl 2 ) treatment and carbon dioxide (CO 2 ) gasifi cation. The activated carbon produced was characterized by BET surface area, porosity development (total pore volume and micropore fraction). Adsorption of Orange G dye (OG) from water was studied using the prepared activated carbon. A three-factor central composite design (CCD) combined with response surface modeling (RSM) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…Mesoporous-activated carbon of various origins was tested for OG [7][8][9][10][11]. The maximum adsorption capacity of these activated carbon adsorbents, from 9.129 to 236.07 mg g −1 [7,8], is still lower than that of some functionalized adsorbents.…”
Section: Introductionmentioning
confidence: 99%
“…Mesoporous-activated carbon of various origins was tested for OG [7][8][9][10][11]. The maximum adsorption capacity of these activated carbon adsorbents, from 9.129 to 236.07 mg g −1 [7,8], is still lower than that of some functionalized adsorbents.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported the synthesis of activated carbons from date stones, often termed date pits [32,33] using phosphoric acid [34], zinc chloride [35], and carbon dioxide [36]. The methodologies of converting date stones into activated carbons have yielded a variety of pollutant-removal applications for this material, such as pesticides [37], dyes [38][39][40], heavy metals [38,41,42], and pharmaceuticals [43,44].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported the production of activated carbons from date stones often termed date pits (Merzougui et al 2011;Danish et al 2014) using phosphoric acid (Girgis and El-Hendawy 2002), zinc chloride (Cherik and Louhab 2017) and carbon dioxide (Suresh Kumar Reddy et al 2013). The methodologies of converting date stones into activated carbons have yielded a variety of pollutant removal applications for this material, such as, pesticides (Hameed et al 2009;Hassan et al 2020), dyes (Al-Ghouti et al 2010Bouchemal et al 2012;Messaoudi et al 2016), heavy metals (Al-Ghouti et al 2010;Bouhamed et al 2012;Mangwandi et al 2020) and pharmaceuticals (Belhamdi et al 2016;Darweesh and Ahmed 2017).…”
Section: Introductionmentioning
confidence: 99%